Within-school spillover effects of foreclosures and student mobility on student academic performance - Katharine Bradbury; Mary A. Burke; Robert K. Triest (Federal Reserve Bank of Boston, 2014)
Aside from effects on nearby property values, research is sparse on how foreclosures may generate negative externalities. Employing a unique dataset that matches individual student records from Boston Public Schools - including test scores, demographics, home address moves, and school changes - with real estate records indicating whether the student lived at an address involved in foreclosure, we investigate the degree to which the test scores of students attending high-foreclosure schools suffer, even among students not directly experiencing foreclosure. We also explore the impact on individual test scores of school-level (by grade and year) student mobility - that is, inflows of new students to a school during the school year - including mobility induced by residential moves (in some cases caused by foreclosures) and mobility arising for other reasons. We find fairly robust evidence that higher student mobility at a school, induced by residential moves, imposes significant negative effects on test scores of students at the receiving school. Beyond this channel, school-level foreclosure prevalence does not appear to generate externalities. Since we also find that residential-moveinduced school changes appear to harm the outcomes of the school-changers themselves, policies that seek to limit such changes within the academic year may uniformly raise test scores, at least in the short run.
Keywords: I20; I24; J24; G21; 330